Antara Menghukum atau Mempermalukan: Suatu Upaya Memodifikasi Perilaku (Pengalaman 6 SMU di Depok, Jawa Barat) - Meliala, Adrianus (UI Scholars Hub, 2004)
Such dilemma between guilt and shameful has been an interesting topic in the field of social psychology since few times ago. That dilemma persists when discussing social control, self-control, individual moral values, moral standard, cross-cultural influence as well as education-related setting. It is predicted, the one which is more influential, whether guilt aspect or shameful aspect, will one way or another influence the way somebody’s behavior can be modified. This study investigates such tendency which prevails in public schools especially performed by pupils when treating their student’s misconduct. Research question forwarded is whether they exploit punishment or to create shaming feeling towards students who have made nuisances in school. The result shows method of punishment has been the only way of modifying behavior which is regarded deviant. Other finding, it is believed that, having given such punishment, shameful feeling will follow. This finding is in association with the character of Indonesian society toward the way guilt and shamefull operate.